Unrevealing Parasitic Trophic Interactions—A Molecular Approach for Fluid-Feeding Fishes - Bonato, Karine O.; Silva, Priscilla C.; Malabarba, Luiz R. (Frontiers in Ecology and Evolution, 2018)
Fish diets have been traditionally studied through the direct visual identification of food items found in their stomachs. Stomach contents of Vandeliinae and Stegophilinae (family Trichomycteridae) parasite catfishes, however, cannot be identified by usual optical methods due to their mucophagic, lepidophagic or hematophagic diets, in such a way that the trophic interactions and the dynamics of food webs in aquatic systems involving these catfishes are mostly unknown. The knowledge about trophic interactions, including difficult relation between parasites and hosts, are crucial to understand the whole working of food webs. In this way, molecular markers can be useful to determine the truly hosts of these catfishes, proving a preference in their feeding behaviour for specific organisms and not a generalist way of life. Sequences of cytochrome oxidase subunit 1 (COI) were successfully extracted and amplified from mucus or scales found in the stomach contents of two species of stegophilines, Homodiaetus anisitsi and Pseudostegophilus maculatus, to identify the host species. The two species were found to be obligatory mucus-feeders and occasionally lepidophagic. Selection of host species is associated to host behaviour, being constituted mainly by substrate-sifting benthivores. Characiformes are preferred hosts, but host choice depends on what characiform species are available in their environments, usually corresponding to the most abundant species. This is the first time that host species of parasitic fishes bearing mucophagous habits are identified, and demonstrates the effectiveness of the extraction and amplification of mitochondrial DNA from the ingested mucus in gut contents. The molecular markers effectively allowed determine parasite preferences and helps in better understanding the food web and trophic interaction on which fish species are involved. Despite, the methodology applied here can be used for an infinitive of organisms improving ecological trophic studies.